Innovative Work Culture And Employee Performance In The Digital Age: A Literature Review - Vera Andini; Havis Aravik (Jurnal Bisnis dan Manajemen (JURBISMAN), 2026)
The digital era demands that organizations not only adopt technology but also build a work culture that supports innovation to improve employee performance. An innovative work culture embodies organizational values that encourage creativity, continuous learning, and rapid response to change. This study conducted a literature review to understand the relationship between an innovative work culture and employee performance in the digital era. Data collection techniques included a literature search of scientific journals and recent publications. The study results indicate that an innovative work culture contributes significantly to increased creativity, technology adaptation, and employee productivity, thus positively impacting individual and organizational performance. Organizations that successfully implement an innovative work culture tend to have superior employee performance in the face of digital change.